Salt-losing syndrome in 2 infants with defective 18-dehydrogenation in aldosterone biosynthesis. - Milla, P J (1977)
Two infants presented with a salt-losing syndrome, the presenting features of which were subtle. One case appeared to be transient. Deficient production of aldosterone was shown by plasma renin activity and plasma aldosterone profile. Gas chromatography-mass spectrometry of urine indicated a defect in 18-dehydrogenation of 18-hydroxycorticosterone. Treatment with salt supplements and 9alpha-fludrocortisone reversed the salt-losing state and in one case treatment was later stopped. Although the disease may appear transient, the biochemical defect is persistent and for adequate growth a positive salt-balance is necessary.